Role of EEG in Measuring Cognitive Reserve: A Rapid Review - Šneidere, Kristı̄ne; Mondini, Sara; Stepens, Ainārs (Frontiers in Aging Neuroscience, 2020)
This review aimed to systematically summarize the possible neural correlates of cognitive reserve thus giving an insight into possible biomarkers for the concept. A total of 44 studies were analyzed in accordance with PRISMA guidelines and four studies were included in further analysis. The results indicated a relationship between P3b waveform and cognitive reserve, while more ambiguous outcomes were found when conducting resting-state EEG. This review indicates the first steps into assessing CR using physiological measures; however, more research is needed to better understand its’ underlying mechanisms.